Effect of Fortification and Fermentation on the Nutritional Value of Sorghum (Sorghum bicolor (L.) Moench) Flour - Bahlawan, Zuhriyan Ash Shiddieqy; Damayanti, Astrilia; Megawati, Megawati; Cahyari, Khamdan; Margiyanti, Yuyun; Mufidati, Muslimatul (Trends in Sciences, 2022)
This study focuses on the effect of fortification with soybean flour and fermentation with Rhizopus oligosporus on the nutrition of sorghum flour. The result shows that pre-treatment by using dilute alkali solution for 10 h could reduce condensed tannins up to 86.92 %. After 60 h of fermentation, the amount of condensed tannins decreased gradually to 0.24 %. The optimum of the fortification and fermentation experiment characterized by 0.29 % of condensed tannins and 9.09 % of crude protein. These values were obtained by using 7.5 % (w/w) of soybean flour fortification and 2.5 % (w/w) of R. oligosporus. The highest swelling power was obtained 8.15 g/g at 95 °C and the water solubility index reaches 26.15 % after fortification and fermentation for 60 h which is caused by changes in the structure of sorghum flour. The proximate analysis shows the results of 79.5 % carbohydrate, 3.1 % fat, 4.8 % moisture content, and 1.6 % ash content. Fermentation using R. oligosporus and fortification with soybean flour is feasible to reduce condensed tannins and increase crude protein with higher functional and good rheological properties of sorghum flour. These results could be a good prospect for substituting wheat flour as an alternative food in the future. HIGHLIGHTS Sorghum is one of the cereals that is rarely used as food because of its high condensed tannin content Soaking using dilute alkali and the fermentation process with Rhizopus oligosporus can reduce the concentration of condensed tannins Fortification with soybean is used to increase the protein value of modified sorghum flour GRAPHICAL ABSTRACT